2020
DOI: 10.1103/physrevresearch.2.013065
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional magnetic field response of the hyperhoneycomb Kitaev magnet βLi2IrO3

Abstract: We present a unified description of the response of the hyperhoneycomb Kitaev magnet β-Li 2 IrO 3 to applied magnetic fields along the orthorhombic directions a, b and c. This description is based on the minimal nearest-neighbor J-K-Γ model and builds on the idea that the incommensurate counter-rotating order observed experimentally at zero field can be treated as a long-distance twisting of a nearby commensurate order with six spin sublattices. The results reveal that the behavior of the system for H a, H b a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(58 citation statements)
references
References 73 publications
4
54
0
Order By: Relevance
“…However, most of these materials exhibit complex long-range magnetic orders at sufficiently low temperatures, indicating that other subdominant interactions between magnetic moments are present and may also have nontrivial bond-dependent character. Both experiment [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and theory [27][28][29][30][31][32][33] have shown that these orders are fragile and can be efficiently suppressed by external magnetic field. It was also found that the competition between the external field and anisotropic bond-dependent exchange interactions gives rise to highly anisotropic magnetization processes and a variety of complex orders at intermediate fields [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of these materials exhibit complex long-range magnetic orders at sufficiently low temperatures, indicating that other subdominant interactions between magnetic moments are present and may also have nontrivial bond-dependent character. Both experiment [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and theory [27][28][29][30][31][32][33] have shown that these orders are fragile and can be efficiently suppressed by external magnetic field. It was also found that the competition between the external field and anisotropic bond-dependent exchange interactions gives rise to highly anisotropic magnetization processes and a variety of complex orders at intermediate fields [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the purpose of this paper is to understand the recent torque measurements in β-Li 2 IrO 3 [26] and γ -Li 2 IrO 3 [12,13]. These two materials appear to have closely related local energetics [35], and we will therefore focus entirely on the hyperhoneycomb β-Li 2 IrO 3 [23][24][25][26]36,37], whose microscopic minimal model, the nearest-neighbor (NN) J-Kmodel, has been better understood [30,31,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…as can be seen from Eq. (18). This is precisely the condition that minimizes the classical energy of the KHAF [40,75,76].…”
Section: Region Ia and Ib : S Ra + S Rb + S Rcmentioning
confidence: 97%
“…Unlike isotropic Heisenberg magnets, these materials break explicitly the SU(2) spin rotational invariance down to a discrete subgroup which is set by the interplay of spin-orbit coupling, crystal field effects and electronic correlations. The resulting anisotropic exchange gives rise to a new type of magnetic frustration, different from geometrical frustration [10,11], a wealth of unusual magnetic orders with strong sensitivity to external perturbations [6,8,[12][13][14][15][16][17][18][19][20], as well as gapped and gapless spin liquids with fractionalized excitations [21]. In addition to the extensively studied layered honeycomb materials α-RuCl 3 , Na 2 IrO 3 and α-Ir 2 IrO 3 , and their 3D analogues (β-γ )-Li 2 IrO 3 , other geometriesincluding triangular, kagome, pyrochlore, hyperkagome and fcc lattices-have attracted a lot of attention because they combine the frustration from the competing exchange couplings with the geometric frustration of the underlying lattices [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%